Penerapan Analisis Dimensi dalam Rancang Bangun Mesin Pembelah Biji Kedelai (Glycine max L.) Sistem Gesek Putar - Rofarsyam Rofarsyam; Bambang Purwantana; Nursigit Bintoro (agriTECH, 2012)
The aim of this research was to design a spin friction type of soybean slicing machine needed in the preparation of tempeh raw material. Dimensional analysis method was used to develop a mathematical relationship between the slicing capacity and its design variables. The prototype was tested using 260 mm diameter of hoppers equiped by number of blades with staggering variations of 51, 102, and 240 mm; a 300 mm diameter of hopper equiped by hopper’s blades with staggering of 118 mm; a 90 mm diamater of rotor with blades spacing of 71 mm; a 180 mm diameter of rotor with blades spacing of 141 mm; and a 75 mm diameter of rotor equiped by blades with spacing of 59 mm. The results showed that the slicing capacity (Q), were infl uenced by mass of soybean (WB), angular velocity (n), mass of water (WA), processing time (t), soybean density (ñ), spacing of rotor blades (SR), length of rotor blades (HR), spacing of hopper blades (SH), length of hopper blades (HH), and hopper diameter (DH). The relation was mathematically expressed by: The slicing capacity (Q/WB.n) were infl unced 620 % by parameters of (DH/SR) and 2 % by (WA/WB). The mathematical equation could be recommended as a reference for determining the geometry and the operational development of soybean slicing machine.ABSTRAKPenelitian ini bertujuan untuk merancangbangun mesin pembelah biji kedelai sistem gesek putar yang diperlukan dalam penyiapan bahan baku pembuatan tempe. Pendekatan analisis dimensi digunakan untuk mendapatkan persamaan matematis yang menghubungkan kapasitas kerja pembelahan dengan parameter-parameter yang berpengaruh. Hasil rancangbangun diuji melalui variasi hopper berdiameter 260 mm dengan jarak sudu masing-masing 51, 102, dan 204 mm; hopper berdiameter 300 mm dengan jarak sudu 118 mm; rotor berdiameter 90 mm dengan jarak sudu 71 mm, rotor berdiameter 180 mm dengan jarak sudu 141 mm dan rotor berdiameter 75 mm dengan jarak sudu 59 mm. Dari hasil pengujian hubungan antara kapasitas pembelahan (Q) terhadap berat kedelai (WB), kecepatan putar (n), berat air (WA), waktu proses (t), massa jenis kedelai (ñ), jarak sudu rotor (SR), panjang sudu rotor (HR), jarak sudu hoper (SH), panjang sudu hoper (HH), dan diameter hoper (DH) adalah sebagai berikut:Pengaruh parameter rancangbangun terhadap kapasitas kerja pembelahan (Q/WB.n) yang paling besar adalah (DH/SR) yaitu sebesar 620 %, yang paling kecil adalah (WA/WB) sebesar 2 %. Model matematis tersebut dapat direkomendasikan sebagai acuan dalam penentuan dimensi dan operasional pengembangan mesin pembelah biji kedelai sesuai kapasitas kerja yang dikehendaki.